Determinants of Banking Credit Default in Indonesia: A Comparative Analysis - Muhammad Imaduddin (Tazkia Islamic Finance and Business Review, 2008)
This study aims to analyze the determinants of Islamic banking credit default compared with conventional banking in Indonesia. This study utilized timeseries analysis, by which ordinary least square method is adopted. 40 monthly data observations from January 2003 until April 2006 are used. The study is divided into two models, namely Islamic banking model and conventional banking model. The values of non-performing financing (NPF) in Islamic banking and non-performing loan (NPL) in conventional banking are treated as the dependent variables. The results showed that two-month lagged of non-performing financing (NPF), total asset (ASSET), the amount of thirdparty-funds (TPF), one-month lagged of total financing (DFIN), and growthof gross-domestic product (GDPG) variables have significant impact to the ratio of non-performing financing (NPF) in Islamic banking. Meanwhile, the three-month lagged of non-performing loan (DDDNPL), total asset (CASSET), three-month as well as two-month period lagged of total loan (DDDCRED and DDCRED), inter-bank money market (PUAB), and growth of gross-domestic (GDPG) are significant to influence the ratio of non-performing loan (NPL) in conventional banking. The result also implied that the general election in 2004 had a significant influence to the ratio of non-performing financing (NPF) in Islamic banking.Even tough from the outset, it seems Islamic banking has a better performance than conventional banking by having a relatively low NPF, this study, however, has found the opposite. Albeit, Islamic banking showing a good long-runas well as short-run dynamics among all variables in the beginning, after modifying the model into autoregressive in the main analysis, results showed that conventional banking has a better performance than Islamic banking with higher correlation of determination. In this regard, we cannot assume thatIslamic banking is performing poorly in managing credit default problems. This is because the result implied that the level of Islamic banking’s R-squared, R-bar-squared and DW values are good. Therefore, although Islamic banking is relatively a new comer in the Indonesian banking industry, it has shown a good performance in the banking credit risk management and can compete head-on with conventional banking, respectively.Keywords: Islamic Banking, Conventional Banking, Indonesia, Credit Default, and Time-Series Analysis